Management of Student Character Education Madrasah Ibtidaiyah Negeri I Kapuas Hulu - Sarono Wijio (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2020)
Basically, a person's success is not determined solely by technical knowledge and abilities, but rather by the ability to manage oneself and others. The research objectives were (1) Application of character education for students of MIN I Kapuas Hulu; (2) The use of character learning designs for students of MIN I Kapuas Hulu; (3) Factors that influence the character of students of MIN I Kapuas Hulu. This research was conducted at Madrasah Ibtidaiyah Negeri I Kapuas Hulu. This type of research is qualitative research. Data collection techniques using interviews, observation and documentation. The results of the study (1) The implementation of character education for students of Madrasah Ibtidaiyah Negeri I Kapuas Hulu, through habituation or school culture such as habituation of shaking hands, saying greetings, praying sunnah dhuha, are activities carried out in a school environment that instill character values ​​by basic concept of mission: carry out moral guidance according to Islamic principles. The stage of implementing the habituation or school culture by directing, inviting, modeling and giving examples; (2) The method of learning the character of students of Madrasah Ibtidaiyah Negeri I Kapuas Hulu, through a variety of methods, by always trying to incorporate material into character values ​​(Reflective). And provide advices, directions, exhortation, tausiyah, to always do good in accordance with Islamic values, which is done before or after or in between the delivery of material; (3) The factors that influence the character of students of Madrasah Ibtidaiyah Negeri I Kapuas Hulu, in character education are a form of support from the family environment (parents), the school environment, and the community environment and other stakeholders, which also influence the values ​​of children's character through the level of attention , compassion, and guidance.